Detection of Sarcocystis aucheniae DNA in placental and umbilical cord tissues suggests possible vertical transmission in domestic South American camelids - Monica Florin-Christensen; Juan Reategui-Ordoñez; Cesar Vargas Tacuri; Luisa Neyra; Carlos V. Enriquez; Evelyn Diaz; Halley Rodriguez Huanca; Ximena Barriga Marcapura; Luis V.M. Olivera; Susana M. Giuliano (Veterinary Parasitology, 2026)

Shrimp (sub-)national traceability and retail fraud detection using stable isotopes and multi-element profiling - V. Deklerck; R.P. Davis; A. Rodriguez-Zunino; S. Khongtanakrittakorn; S. Hofem; J. Jungkeit; A. Leyton; M. Osorto-Nuñez; C. Podmore; L. Prior; C.C. Smith; B. Soule; et al. (Food Control, 2026)

GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Hybrid Sparrow Search Algorithm Support Vector Machine Regression Bidirectional Long-Short Term Memory (SSA-SVR-BiLSTM) model with Lagrange-based weighting for PM$$_{2.5}$$ prediction and stratified evaluation - Maria Fernanda Camargo; Sergio Diaz; Ricardo Elias Celis Parra; Vladimir Ramírez Tarazona; Astrith Eugenia Rincón Sánchez; V. Rodriguez-Rueda; Omar F. Rojas-Moreno; Alejandra Baena (Environmental and Ecological Statistics, 2026)
Air pollution is a major environmental risk to public health, strongly associated with cardiovascular and respiratory diseases. According to the World Health Organization, at least 99% of the global population lives in areas that do not meet its air-quality guidelines. PM $$_{2.5}$$ 2.5 variability reflects the interaction between local emission sources and meteorological processes that regulate near-surface dispersion and accumulation, producing nonlinear temporal patterns that motivate hybrid modeling approaches. We propose an SSA-SVR-BiLSTM framework for short-term PM $$_{2.5}$$ 2.5 forecasting that combines SSA-optimized SVR and BiLSTM models within a constrained linear ensemble with weights estimated exclusively on the validation partition using Lagrange multipliers. The model is evaluated on 10 months of high-frequency (5-min) air-quality and meteorological data collected at a traffic-influenced monitoring site in Duitama, Colombia. On the held-out test set, the hybrid achieved $$R^2 = 0.9585$$ R 2 = 0.9585 and MAPE $$= 7.62%$$ = 7.62 % , outperforming five of six SSA-optimized baselines; the difference relative to the best individual model (SSA-SVR was statistically significant but practically negligible ( $$p = 0.0105$$ p = 0.0105 , $$Δ R^2 = 0.0002$$ Δ R 2 = 0.0002 ), and the value of the hybrid lies primarily in its improved consistency across low and medium concentration regimes rather than in a large global accuracy gain. Stratified evaluation across concentration regimes and normative thresholds (WHO, EPA) revealed systematic underestimation at extreme pollution episodes, a structural limitation shared by all evaluated models. A feature occlusion analysis identified PM $$_5$$ 5 and PM $$_{10}$$ 10 as the dominant exogenous predictors (53.6 and 21.7%), with meteorological variables contributing an additional $${\sim }20%$$ ∼ 20 % of the total relevance.

On the Possibility of Ionospheric Memory Over the Low-Latitude Mexican Region - M. A. Sergeeva; I. D. Orrala-Legorreta; E. Rodriguez-Orozco; J. H. Castro-Chacon; O. A. Maltseva; J. A. Gonzalez-Esparza; P. Corona-Romero; V. J. Gatica-Acevedo; M. Pazos; M. E. Gonzalez-Alvarez; R. Bonifaz; A. Melgarejo-Morales; et al. (Pure and Applied Geophysics, 2026)
Features of possible regional ionospheric memory manifested themselves at low-latitudes under solar eclipse conditions.

Comparative evaluation of sperm quality assessment methods in purebred spanish horses - N. Latorre; C. Gómez-Cuétara; E. Cañizares; F. Crespo; V. Pérez-Aguilera; M. Iniesta Cuerda; J.A. Laborda-Gomariz; A.J. Soler; E.R.S. Roldan; A. Sanchez-Rodriguez (Journal of Equine Veterinary Science, 2026)

Xylem tissue-inspired sustainable foams from selectively toughened poly(l-lactide)/polycarbonate blends - Anthony V. Tuccitto; Nello D. Sansone; Neelima Tripathi; Rafaela Aguiar; Arturo Rodriguez-Uribe; Amar K. Mohanty; Manjusri Misra; Patrick C. Lee (Chemical Engineering Journal, 2026)

Morphology and particle size distribution in the indoor dust: A hidden threat to human health? - D. Meza-Figueroa; E. Vega; J. Entwistle; A. Angulo-Molina; A. Valencia-Meza; B. Schiavo; V. Rodriguez; B. González-Grijalva; F. Berrellez-Reyes; C. Ortega-Rosas; A. Wellens; A. Namdeo (Environmental Geochemistry and Health, 2026)

Ground level enhancement GLE #77 on 11 November 2025: a data summary - A.L. Mishev; B. Heber; K.-L. Klein; R. Vainio; H. Mavromichalaki; O. Raukunen; N. Larsen; N. Petrov; N. Nikonov; S. Masson; M. Pesce-Rollins; B.T. Kress; et al. (Advances in Space Research, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Interspecific SCNT in yak followed by embryo aggregation improves early in vitro developmental parameters without restoring pluripotent gene expression - M. Yauri Felipe; M. Duque Rodriguez; A. De Stefano; L.D. Ratner; V. Alberio; D.F. Salamone (Theriogenology, 2026)

Standardising research on marine biological carbon pathways required to estimate sequestration at Polar and sub-Polar latitudes - Simon A. Morley; David K.A. Barnes; Camila Neder; Ricardo Sahade; Chester J. Sands; Carla M. de Aranzamendi; Kaja Balazy; Piotr Balazy; Facundo Barrera; Narissa Bax; Sofia Becerra; Lucia Bergagna; et al. (Earth-Science Reviews, 2026)

Hydraulic Fracture Propagation in Pre-structured Media: Stress Field and Fracture Network Topology - Adrian V. Garcia; Rached M. Rached; Carlos D. Rodriguez-Hernandez; J. Carlos Santamarina (Rock Mechanics and Rock Engineering, 2026)

Contributions to the knowledge of DNA barcodes and diversity of intertidal and shallow-water mollusks in the Beagle Channel - L. D. Chiberry; J. Sánchez; V. M. Núñez; S. Rodriguez; M. Pellegrino; S. Poljak (Polar Biology, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Physicochemical Differences Observed in Photostability Studies of Lyophilized, Reconstituted, and Diluted Somatropin - Jordan D. Pritts; Uriel Ortega-Rodriguez; V. Ashutosh Rao (Pharmaceutical Research, 2026)
Background While photostability testing conditions for biologics are often based on small molecule standards, the unique characteristics of proteins necessitate a deeper understanding of appropriate testing and controls. This study examines the effects of light stress on various presentations of somatropin, a therapeutic growth hormone. Methods Somatropin was exposed to light in lyophilized, reconstituted, and diluted forms. Quality attribute changes were analyzed using size exclusion chromatography, micro-fluidic imaging, imaged capillary isoelectric focusing, and liquid chromatography mass spectrometry (LC–MS). Results Light stress increased high molecular weight species (HMWS), particularly in liquid formulations, as shown by size exclusion chromatography (Lyophilized + 0.4%, Reconstituted + 2.7%, Diluted + 4.7%). Micro-fluidic imaging revealed no change in particle formation. All presentations exhibited shifts in charge variants, with increases in acidic species (Lyophilized + 2.8%, Reconstituted + 7.8%, Diluted + 6.2%) and basic (Lyophilized + 0.4%, Reconstituted + 0.7%, Diluted + 0.8%) . Liquid chromatography-tandem mass spectrometry (LC–MS/MS) peptide mapping detected increased methionine oxidation in light-exposed samples, correlating with higher protein concentration (M14- Lyophilized + 2.3%, Reconstituted + 7.4%, Diluted + 2.7%, M125- Lyophilized + 2.5%, Reconstituted + 2.9%). Diluted somatropin showed higher HMWS levels but reduced methionine-125 oxidation susceptibility compared to reconstituted formulations. Conclusions Light exposure altered product quality attributes, with more pronounced effects on liquid presentations. These findings provide insights into the distinct impacts of light exposure on different drug presentations throughout their lifecycle, highlighting the importance of tailored photostability testing for different product presentations of biologic drugs.

Covalent organic framework-coated alumina for the removal of geosmin from water in recirculating aquaculture systems - Ana Vieira; Joana Araújo; Pablo Blanco Canella; Silvia Escudero-Curiel; Soraia P.S. Fernandes; Laura Rodriguez-Lorenzo; Juliana P.S. Sousa; Liliana P.L. Gonçalves; Salomé G.P. Soares; Marta Pazos; M. Ángeles Sanromán; Yury V. Kolen’ko; et al. (Journal of Environmental Chemical Engineering, 2025)

A Simple Model to Estimate the Economic Optimum Nitrogen Rate in Potato Using Vegetation Indices - Claudia M. Giletto; W. D. Carciochi; F. M. Inchauspe; S. E. Silva; M. N. Cassino; V. Ortega; S. Rodriguez; J. C. Laborde Amador; N. Reussi Calvo (Potato Research, 2025)

Correction to: Hydrogeochemical Evaluation of an Urban Aquifer Under Stress: Rare Earth Elements Fractionation and Human Health Implications - K. M. Ochoa-Guerrero; P. F. Rodriguez-Espinosa; E. Martinez-Tavera; V. Balaram; M. P. Jonathan (Environmental Management, 2025)

Hydrogeochemical Evaluation of an Urban Aquifer Under Stress: Rare Earth Elements Fractionation and Human Health Implications - K. M. Ochoa-Guerrero; P. F. Rodriguez-Espinosa; E. Martinez-Tavera; V. Balaram; M. P. Jonathan (Environmental Management, 2025)

An integrative urban tree risk index as a novel framework for risk assessment: A case study of Montreal, Canada - Manuel Esperon-Rodriguez; Annick St-Denis; Julie Messier; Rachael V. Gallagher; Mark G. Tjoelker; Christian Messier (Urban Forestry & Urban Greening, 2025)

The role of emersion time in modulating biomarker responses to pollution in intertidal mollusks - María V. Laitano; Clara Liebana; Ivana S. Friedman; Yamila E. Rodriguez (Marine Environmental Research, 2025)

Assessment of microplastic retention efficiency using pilot-scale filtration systems applied to drinking water - K. Herrera; A. Egea-Corbacho; D. Coello; J. Quiroga; E. Marin; V. Monsalvo; E. Lucero; R. Rodriguez (Journal of Hazardous Materials, 2025)

Evaluating the combined methods of live planting and seed dispersal in restoration of Zostera marina (eelgrass) in Barnegat Bay, New Jersey by genetic diversity and pedigree analysis of restored populations - Nicole Rodriguez Ortiz; Nathan Cruz; Tiffany V. Santos; Paul A.X. Bologna; James J. Campanella (Aquatic Botany, 2025)

Discovery of Latissimia ningalooensis: a new invasive soft coral species in Puerto Rico - Daniel A. Toledo-Rodriguez; Catherine S. McFadden; Nilda M. Jimenez Marrero; J. David Muñoz-Maravilla; Alex J. Veglia; Ernesto Weil; Nikolaos V. Schizas (Biological Invasions, 2025)

Disease prevalence in confiscated exotic and indiginous birds and reptiles housed in a cites-authorized rescue center in Spain - M. Jimenez Martinez; A. Martin; A. Rabanal Soto; V. Hidalgo Martinez; A. Rodriguez Luis; M. Aranda Vazquez; J. De Andres Gamazo (Journal of Comparative Pathology, 2025)

Development of a biotechnological process for the production of recombinant canine interferon-alpha using the baculovirus-insect cell and larvae system - Maria S. Rodriguez; Ignacio Smith; Marcela S. Villaverde; Joaquin M. Birenbaum; Joaquin Poodts; Federico J. Wolman; Alexandra M. Targovnik; Maria V. Miranda (Biotechnology Letters, 2025)

Evidence for cryptic sulfur cycling in Atlantic ocean sediments affected by aeolian dry deposition of Saharan dust - Tomas Israel Grijalva-Rodriguez; Alexandra V. Turchyn; Sharon Albin; Efrat Eliani-Russak; Alen Manashirov; Irina Zweig; Alexey Kamyshny (Frontiers in Marine Science, 2025)
Cryptic sulfur cycling, characterized by nearly quantitative oxidation of hydrogen sulfide, is characteristic for sediments with low organic matter and high reactive iron contents. A common source of reactive iron in sediments of marine systems that are located in arid environments is aeolian dry deposition of desert dust. The presence of such a cryptic sulfur cycle has previously been documented in sediments of enclosed basins such as the Red Sea and, especially, in its north-eastern extension, the Gulf of Aqaba. Here we present speciation data for iron, manganese and sulfur as well as the isotopic composition of sulfate, and demonstrate cryptic sulfur cycling in sediments from the north-east Atlantic Ocean situated in the vicinity of the Sahara. These sediments are characterized by high reactive-to-total-iron ratios and extremely low sulfur-bound iron contents. In the near-shore sediments (e.g., sediments which were sampled at < 550 km from the coast) highly reactive iron contents are higher than in the sediments, which were retrieved at higher distances from the continent. In the near-shore sediments, the most abundant highly reactive iron fraction is dithionite-extractable iron, which comprises goethite, hematite, and akaganéite. This is the most abundant group of minerals in the Saharan dust collected above the Red Sea. On the other hand, contents and speciation of highly reactive iron does not significantly affect sedimentary sulfur-bound iron contents. We suggest that cryptic sulfur cycling is a common phenomenon for sediments in the ocean situated near arid environments.

P20-17 Polyethylene terephthalate (PET) nanoplastics induce acute pulmonary inflammation in mice - Ø.P. Haugen; L.M.A. Camassa; H.F. Berntsen; F.-C. Lin; V. Alcolea-Rodriguez; R. Portela; F. Barbero; O.A.H. Foss; H. Sadeghiankaffash; Ø. Skare; S. Alsaedi; A.L. Moen; et al. (Toxicology Letters, 2025)

Soil salinity effects on inter-plant signalling in wild cotton are contingent on herbivore load and differentially shape direct and indirect defences - Jonathan Interian-Aguiñaga; Uriel Solís-Rodriguez; Yeyson Briones-May; Patricia Guadarrama-Chávez; Marine Mamin; Mary V. Clancy; Ted C. J. Turlings; Xoaquín Moreira; Luis Abdala-Roberts (Planta, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Shadows over Caribbean reefs: occurrence of a new invasive soft coral species, Xenia umbellata, in southwest Puerto Rico - Daniel A. Toledo-Rodriguez; Alex J. Veglia; Nilda M. Jimenez Marrero; Joyce M. Gomez-Samot; Catherine S. McFadden; Ernesto Weil; Nikolaos V. Schizas (Coral Reefs, 2025)

Global trends in urban forest irrigation: Environmental influences, challenges and opportunities for sustainable practices across 109 cities worldwide - Manuel Esperon-Rodriguez; Rachael V Gallagher; Alessio Russo; Sally A Power; Pedro Calaza-Martínez; Tiago Capela Lourenço; Paloma Cariñanos; Ana Alice Eleuterio; Zhengfei Guo; Gervais Lee; Pierre Masselot; Robert I. Mcdonald; et al. (Sustainable Cities and Society, 2025)

Correction: Parasite diversity in sea turtles of the temperate SW Atlantic: a bridge between systematics and ecology - E. O. Palumbo; C. K. Álvarez; S. Rodriguez-Heredia; A. Rosenthal; M. Vassallo; I. M. Bruno; J. Loureiro; L. Diaz; A. Faiella; M. R. Werneck; J. I. Diaz; V. González Carman (Marine Biology, 2025)

Exploring Nutritional Condition of Merluccius hubbsi During Early Life Stages: Environmental Drivers and Possible Implications on Subsequent Recruitment - Julieta Rodriguez; Nadia M. Alves; Harold Fenco Chavesta; Gustavo J. Macchi; Agustin Schiariti; Rosana Di Mauro; Marina V. Diaz (Fisheries Oceanography, 2025)
The early life stages of fish represent a period of high energy requirements due to profound changes that characterize the passage to adulthood, crucial for fisheries recruitment. This study focuses on the North Patagonian Frontal System (NPFS) that guarantees successful larval development and fulfills the three postulates of Bakun's “fundamental triad” in regards to nutrients, concentration of food, and retention of eggs and larvae inside the favorable area. The objective was to evaluate the nutritional condition of Merluccius hubbsi larvae and juveniles, from the Patagonian stock in January during austral summer (2010–2021). The standardized RNA/DNA index (RDs) was used. Interannual variation in the larval condition was observed in relation to NPFS features. RDs were positively linked to the stratification of the water column in the stratified zone. An opposite trend was observed between larval condition and potential egg production that might indicate the existence of density‐dependent mechanisms. On the other hand, the positive relation between larval condition and egg production of older females (≥7 years) supports the idea of a maternal effect on larval survival. There was also a positive relationship between juveniles condition, body size, and recruitment, but no relationship was observed with the stratification of the water column. The high sensitivity of the RDs index links physiological state with survival probability, informing on factors affecting eggs, larvae, and juveniles until their posterior recruitment. This study identified the stratified area of the NPFS as a favorable nursery zone, providing crucial information for managing populations under high fishing pressure.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Parasite diversity in sea turtles of the temperate SW Atlantic: a bridge between systematics and ecology - E. O. Palumbo; C. K. Álvarez; S. Rodriguez-Heredia; A. Rosenthal; M. Vassallo; I. M. Bruno; J. Loureiro; L. Diaz; A. Faiella; M. R. Werneck; J. I. Diaz; V. González Carman (Marine Biology, 2025)

A novel alternative fate for shrimp fishery wastes as active ingredients in ecofriendly antifouling paints - María V. Laitano; Yamila E. Rodriguez; Guadalupe Rivero; Analía V. Fernández-Gimenez; Guillermo Blustein (Environmental Science and Pollution Research, 2025)

Feed intake, preferences, in vivo digestibility, and nutritional value of tedera (B. bituminosa var. bituminosa) and maralfalfa (Pennisetum purpureum) in Canary sheep - M. Barbera; V. Mendoza-Grimón; J. Espinosa; E. Rodriguez-Ponce; A. Gracia; E. SanJuán; M. R. Ventura (Tropical Animal Health and Production, 2025)
This study evaluated the nutritional value and energy content of tedera ( B. bituminosa var. bituminosa ) and maralfalfa ( Pennisetum purpureum ) through analyses of chemical composition, digestibility, intake, and preference trials. Tedera was compared with maralfalfa and alfalfa hay ( Medicago sativa ). Tedera showed higher crude protein (193 g CP/kg DM) and estimated energy (10.5 MJ DE/kg DM) but lower dry matter (286.3 g DM/kg) and neutral detergent fiber (373 g NDF/kg DM) than both maralfalfa and alfalfa hay. The in vitro organic matter digestibility (IVOMD) of tedera was 61.7%, compared to 51.0% for alfalfa hay and 66.3% for maralfalfa. Digestible organic matter (DOM) ranged from 467 g/kg DM in alfalfa hay to 566.4 g/kg DM in tedera. Four Canary sheep with a mean body weight (BW) of 42.2 ± 5.0 kg were used for digestibility and preference trials. The live weights of the sheep were recorded at the start and end of the 12-day trial. Feed offered and refusals were weighed and recorded daily for eight days, while feces were collected for four days to calculate apparent in vivo digestibility. For tedera, the apparent in vivo OM digestibility, estimated digestible energy, and digestible organic matter were 69.4%, 11.8 MJ/kg DM, and 637.7 g/kg DM, respectively. Preference and feed intake were compared between tedera, maralfalfa and alfalfa hay. Total DM consumption was 1091.3 g/day (tedera + maralfalfa + alfalfa hay), with alfalfa hay intake representing 40.8%, maralfalfa 37.3%, and tedera 21.9% of the total DM consumed. However, no significant differences were observed in the ratio of forages consumed/offered (44.8% for tedera and 51.8% for maralfalfa) or in the total grams of DM, CP, and MJ/kg of DE consumed by the sheep with both forages. The sheep adopted different feeding strategies in response to the chemical composition and nutritive value of the forages. Preferences and intake in this trial were associated with high NDF content in maralfalfa and alfalfa hay and with the high CP content in tedera rather than digestibility results. This may be due to the complementarity of the three forages and the higher CP content in tedera affecting intake. Nevertheless, tedera and marafalfa could be a good forage considering its nutritive value, digestibility, and proven growth performance in herbivores.

Model Organoids: Integrated Frameworks for the Next Frontier of Healthcare Advancements - Riya Bhattacharya; Debajyoti Bose; Tanveen Kaur; Rushik Patel; Oladri Renuka; Raul V. Rodriguez (Stem Cell Reviews and Reports, 2025)

Phytoremediation potential of Tripogandra diuretica for chromium and lead contaminated soils - S. Carusso; N. Rodriguez; Á. B. Juárez; Y. El Kassisse; V. Rodriguez Salemi; L. I. de Cabo (International Journal of Environmental Science and Technology, 2025)

Bridges monitoring and assessment using an integrated bim methodology - D. Rodriguez Polania; F. Tondolo; A. Osello; M. Piras; V. Di Pietra; N. Grasso (Innovative Infrastructure Solutions, 2025)
Risk assessment of long-existing infrastructure has become one of the main challenges in civil engineering. Major efforts have been made in recent years to develop new techniques for rapid damage identification and ensure proper management of these structures. This paper presents a data management approach utilizing BIM methodology to create a digital database for bridge monitoring procedures. Initially, two BIM methodologies for creating a damage database are introduced, focusing on beams from a dismantled urban viaduct. Subsequently, the most suitable methodology is applied to an existing bridge in Turin, Italy. Through the chosen methodology a damage identification and classification process based on a triangular mesh is performed, assisted by a convolutional neural network (CNN) for automatic damage detection. Additionally, the paper outlines a digitalization process within a BIM environment, integrating official guidelines for bridge risk evaluation, classification, and monitoring in Italy. By employing programming tools, all data required by the guidelines is efficiently incorporated into the database. The outcomes demonstrate the effectiveness of remote sensing applications for bridge inspection and the possibility of merging BIM methodology into the inspection process to enhance the damage assessment of existing structures.

Promoting Workplace Health, Safety, and Well-Being Among Essential Agricultural Workers Through Vaccine-Preventable Infectious Diseases Training in the Rio Grande Valley - Anabel Rodriguez; David I Douphrate; Ana L Pineda Reyes; Susana Zavala; Andrea V. Cabrera Cruz; Maria D Alegria; Brian Ukaegbu; Annie J Keeney; Brenda Berumen-Flucker; Eva M Shipp; Shannon P Guillot-Wright; Maria E Fernandez-Esquer; et al. (Journal of Agromedicine, 2025)

Microplastics in the digestive tract of an endangered cetacean of the Southwest Atlantic Ocean: The franciscana dolphin - Antonella D. Padula; Ana C. Ronda; Lucas S. Rodríguez Pirani; A. Lorena Picone; Rosana M. Romano; Gisela V. Giardino; Juan Pablo Seco Pon; Rodrigo Machado; Marcela Gerpe; Diego Rodriguez; Pablo Denuncio (Marine Pollution Bulletin, 2025)

Modeling MBR fouling: A critical review analysis towards establishing a framework for good modeling practices - V. Sandoval-García; M.V. Ruano; M. Alliet; C. Brepols; J. Comas; J. Harmand; M. Heran; G. Mannina; I. Rodriguez-Roda; I. Smets; A. Robles (Water Research, 2025)

Coral-killing and competitive sponges in Nusa Dua, Bali, Indonesia - Dwi Haryanti; Alifalah T. Cahyadi; Fitri F.N. Al Haliim; Hafidza Mahira; Erin Karissa; Anindya Wirasatriya; Pariama Hutasoit; Diah P. Wijayanti; Munasik Munasik; Maria V. Baria-Rodriguez; Ardiansyah D. Puryajati (Regional Studies in Marine Science, 2024)

FreshLanDiv : A Global Database of Freshwater Biodiversity Across Different Land Uses - Minghua Shen; Roel van Klink; Alban Sagouis; Danielle K. Petsch; Deborah Atieno Abong'o; Janne Alahuhta; Salman Abdo Al‐Shami; Laura Cecilia Armendáriz; Mi‐Jung Bae; Tiago Octavio Begot; Jerome Belliard; Jonathan Peter Benstead; et al. (Global Ecology and Biogeography, 2024)
Motivation Freshwater ecosystems have been heavily impacted by land‐use changes, but data syntheses on these impacts are still limited. Here, we compiled a global database encompassing 241 studies with species abundance data (from multiple biological groups and geographic locations) across sites with different land‐use categories. This compilation will be useful for addressing questions regarding land‐use change and its impact on freshwater biodiversity. Main Types of Variables Contained The database includes metadata of each study, sites location, sample methods, sample time, land‐use category and abundance of each taxon. Spatial Location and Grain The database contains data from across the globe, with 85% of the sites having well‐defined geographical coordinates. Major Taxa and Level of Measurement The database covers all major freshwater biological groups including algae, macrophytes, zooplankton, macroinvertebrates, fish and amphibians.

Authentication of grated hard cheeses and quantification of adulteration by FT-NIR spectroscopy and multivariate analysis - Lucas G. Visconti; Paulo Henrique Gonçalves Dias Diniz; David Douglas de Sousa Fernandes; María S. Rodriguez; Carolina V. Di Anibal (International Dairy Journal, 2024)

Diving into the metabolic interactions of titanium dioxide nanoparticles in “Sparus aurata” and “Ruditapes philippinarum” - Mário Jorge Araújo; María Vazquez; Laura Rodriguez-Lorenzo; Antonio Moreda-Piñeiro; Elza Fonseca; Natalia Mallo; Ivone Pinheiro; Monica Quarato; Elizabeth Bigorra-Ferré; Ana Matos; Aldo Barreiro-Felpeto; Maria V. Turkina; et al. (Environmental Pollution, 2024)

Predation on Live and Artificial Insect Prey Shows Different Global Latitudinal Patterns - Elena L. Zvereva; Benjamin Adroit; Tommi Andersson; Craig R. A. Barnett; Sofia Branco; Bastien Castagneyrol; Giancarlo Maria Chiarenza; Wesley Dáttilo; Ek del‐Val; Jan Filip; Jory Griffith; Anna L. Hargreaves; et al. (Global Ecology and Biogeography, 2024)
Aim Long‐standing theory predicts that the intensity of biotic interactions increases from high to low latitudes. Studies addressing geographic variation in predation on insect prey have often relied on prey models, which lack many characteristics of live prey. Our goals were to explore global latitudinal patterns of predator attack rates on standardised live insect prey and to compare the patterns in predation on live insects with those on plasticine prey models. Location Global forested areas. Time Period 2021–2023. Major Taxa Arthropods, birds. Methods We measured predation rates in 43 forested locations distributed across five continents from 34.1° S to 69.5° N latitude. At each location, we exposed 20 sets of three bait types, one set per tree. Each set included three live fly larvae (maggots), three live fly puparia and three plasticine models of the puparia. We used glue rings to isolate half of the sets from non‐flying predators. Results Arthropod attack rates on plasticine prey decreased linearly from low to high latitudes, whereas attack rates on maggots had a U shaped distribution, with the lowest predation rates at temperate latitudes and the highest rates at tropical and boreal latitudes. This difference emerged from intensive predator attacks on live maggots, but not on plasticine models, in boreal sites. Site‐specific attack rates of arthropod predators on live and plasticine prey were not correlated. In contrast, bird attack rates on live maggots and plasticine models were positively correlated, but did not show significant latitudinal changes. Main Conclusions Latitudinal patterns in predation differ between major groups of predators and between types of prey. Poleward decreases in both arthropod and combined arthropod and bird predation on plasticine models do not mirror patterns of predation on our live prey, the latter likely reflecting real patterns of predation risk better than do patterns of attack on artificial prey.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

The presence of two distinct mitochondrial lineages in the bottlenose dolphin (Tursiops truncatus) in Puerto Rico and their affinities with previously reported lineages - Grisel Rodriguez-Ferrer; Richard S. Appeldoorn; Antonio A. Mignucci-Giannoni; Renaldo Rinaldi; Nikolaos V. Schizas (Mammalian Biology, 2024)

Transcriptomic responses to hypoxia in two populations of eastern oyster with differing tolerance - Emma L. Crable; Heather Rodriguez; Rujuta V. Vaidya; Nicholas Coxe; Jerome F. La Peyre; Morgan W. Kelly (Frontiers in Marine Science, 2024)
The eastern oyster, Crassostrea virginica , is a keystone species native to the Gulf of Mexico and Atlantic coasts of the United States and Canada. It provides habitat for other marine organisms and makes up the majority of oyster production in the United States. Despite its tolerance to hypoxic conditions, C. virginica is threatened by anthropogenic climate change, which is increasing both average temperature and the frequency and severity of hypoxic events. In this study, we explore the differences in hypoxia-transcriptional response between two populations of eastern oysters with known differences in hypoxia tolerance at three time points over the course of a 5-day hypoxia treatment. We identified sets of genes involved in the hypoxia response and found differences in both the timing and baseline expression of hypoxia-responsive genes between tolerant and sensitive populations, consistent with a scenario of local adaptation. Analysis of differential gene expression between the two populations and conditions revealed two gene modules with higher baseline expression of hypoxia-sensitive genes in the more hypoxia tolerant population. Key GO terms for genes corresponding to differences between populations include DNA repair, ribosome biogenesis, and ribonucleotide binding. Our results imply that differences in hypoxia tolerance between populations could be due to genetic frontloading of hypoxia response pathways in the more tolerant population.

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

What's that smell? The putrid scent of Rafflesia consueloae, its origin and developmental regulation - Erika Marie A. Bascos; Edwino S. Fernando; Melizar V. Duya; Lillian Jennifer V. Rodriguez (Flora, 2024)

Influence of wildfires on the conflict (2006–2022) in eastern Ukraine using remote sensing techniques (MODIS and Sentinel-2 images) - Fernando Rodriguez-Jimenez; Ana Novo; Joanne V. Hall (Remote Sensing Applications: Society and Environment, 2024)

Mapping the climate risk to urban forests at city scale - Manuel Esperon-Rodriguez; Rachael V. Gallagher; Niels Souverijns; Quentin Lejeune; Carl-Friedrich Schleussner; Mark G. Tjoelker (Landscape and Urban Planning, 2024)

Ataxia-telangiectasia in Latin America: clinical features, immunodeficiency, and mortality in a multicenter study - Renan A. Pereira; Ellen O. Dantas; Jessica Loekmanwidjaja; Juliana T. L. Mazzucchelli; Carolina S. Aranda; Maria E. G. Serrano; Elisabeth A. De La Cruz Córdoba; Liliana Bezrodnik; Ileana Moreira; Janaira F. S. Ferreira; Vera M. Dantas; Valéria S. F. Sales; et al. (Immunologic Research, 2024)

Wide climatic niche breadth and traits associated with climatic tolerance facilitate eucalypt occurrence in cities worldwide - Manuel Esperon‐Rodriguez; Mark G. Tjoelker; Jonathan Lenoir; Bree Laugier; Rachael V. Gallagher (Global Ecology and Biogeography, 2024)
Aim Eucalypts are important and popular urban tree species across cities worldwide. However, little is known about how their climatic niche breadth (CNB) and functional traits predict their success, and vulnerability, to current climate change in cities. We assessed the relationship between the CNB of eucalypts and key traits to understand their tolerance to climate change. Location Global urban areas, 66 cities in 21 countries. Time period 1981 to 2022. Major species studied Fifty ‘eucalypt’ species belonging to the genera Eucalyptus , Angophora and Corymbia . Methods We used the species' safety margin concept to determine cities where eucalypts were planted outside the limits of their CNB, as defined from the native range, considering two extreme variables, maximum temperature of the warmest month (MTWM) and precipitation of the driest month (PDM). We assessed correlations between functional traits (leaf δ 13 C, leaf dry mass, leaf length, leaf N per dry mass, wood density) and negative safety margins, indicative of tolerance to non‐native conditions. Results In total, 42 species planted in 40 cities exceeded their safety margins for MTWM, while 43 species in 38 cities exceeded their safety margins for PDM. Within 24 cities, all species exceeded their native CNB for both MTWM and PDM. The cities of Atakpame (Togo), Chennai (India), Chongqing (China) and the US cities of Phoenix and Riverside had the highest richness of eucalypt species growing outside their native CNB. Broadly, species with wide CNB, small leaves, high δ 13 C, high leaf N per dry mass and high wood density were more likely to persist in cities where climatic conditions exceeded their native CNB. Main conclusions Eucalypts occupy many cities experiencing climatic conditions outside their native CNB. Species with traits characteristic of heat and drought tolerance are more often planted in cities where climatic conditions may exceed their CNB native limits.

Evaluation of imidacloprid (Confidor OD®) genotoxicity in Chrysoperla externa eggs (Neuroptera: Chrysopidae) through comet assay - Fernández Acevedo V; Rodriguez Gil S; Seoane A; Minardi G; M.I. Schneider (Chemosphere, 2024)

Like noodles in a soup: Anthropogenic microfibers are being ingested by juvenile fish in nursery grounds of the Southwestern Atlantic Ocean - Nadia M. Alves; Julieta Rodriguez; Rosana Di Mauro; Julieta S. Rodríguez; David Maldonado; Mara S. Braverman; Brenda Temperoni; Marina V. Diaz (Marine Pollution Bulletin, 2024)

Enabling particle transport on CAD-based geometries for radiation simulations with penRed - S. Oliver; S. Rodriguez Bosca; V. Giménez-Alventosa (Computer Physics Communications, 2024)

Engineered separator of cellulose/ionic-liquid for the fabrication of a novel device with H-type architecture and dual function: Supercapacitor and NO2 gas sensor - L. Ojeda; A. Molina; K.P. Padmasree; A.I. Mtz-Enriquez; A. Zakhidov; V. Rodriguez-Gonzalez; J. Oliva (Chemical Engineering Journal, 2024)

Short-term associations between fine particulate air pollution and cardiovascular and respiratory mortality in 337 cities in Latin America - Nelson Gouveia; Jordan L. Rodriguez-Hernandez; Josiah L. Kephart; Ana Ortigoza; Ricardo Morales Betancourt; Jose Luis Texcalac Sangrador; Daniel A. Rodriguez; Ana V. Diez Roux; Brisa Sanchez; Goro Yamada (Science of The Total Environment, 2024)

A non-invasive method of microplastics pollution quantification in green sea turtle Chelonia mydas of the Mexican Caribbean - Dalila Aldana Aranda; Pauline Sindou; Juan V. Cauich Rodriguez; Gisela Maldonado Saldaña; Rossana Faride Vargas Coronado; Wendy Donaji Nicolás González; Martha Enríquez Díaz; Víctor Castillo Escalante (Marine Pollution Bulletin, 2024)

Holocene organic matter composition in relation to relative sea level stands and associated morphometric changes of a lagoonal system - V. Carvalho; L. Gonzalez; C. Bueno; C. Segura; S.R. Bottezini; A. Leonhardt; D. Diniz; P. Dentzien-Dias; L. Perez; H. Evangelista; M.V. Licínio; H. Inda; et al. (Marine Geology, 2024)

Exploring fishery waste potential as antifouling component - Juliana Lenchours Pezzano; Yamila E. Rodriguez; Analía V. Fernández-Gimenez; María V. Laitano (Environmental Science and Pollution Research, 2024)

A solar evaporator fabricated from corncob waste for the desalination of seawater and removal of oil/herbicides from contaminated water - E. Valadez-Renteria; J. Oliva; A.I. Oliva; M.A. Ruiz-Gomez; A. Encinas; V. Rodriguez-Gonzalez (Chemosphere, 2024)

Effect of biosolid compost amended on Pb availability in soils cultivated with lettuce - M. E. Gómez; G. V. Ferreyroa; M. J. Salazar; M. L. Pignata; J. H. Rodriguez (International Journal of Environmental Science and Technology, 2024)

Simulated gastrointestinal digestion of polylactic acid (PLA) biodegradable microplastics and their interaction with the gut microbiota - C. Jiménez-Arroyo; A. Tamargo; N. Molinero; J.J. Reinosa; V. Alcolea-Rodriguez; R. Portela; M.A. Bañares; J.F. Fernández; M.V. Moreno-Arribas (Science of The Total Environment, 2023)

Bokashi fermentation of brewery’s spent grains positively affects larval performance of the black soldier fly Hermetia illucens while reducing gaseous nitrogen losses - Marco Gebiola; Michael V. Rodriguez; Alexandro Garcia; Andrea Garnica; Jeffery K. Tomberlin; Francesca M. Hopkins; Kerry E. Mauck (Waste Management, 2023)

Alkaline pretreatment of a polymetallic sulfide (Fe-Pb-Mn) ore containing silver increases the efficiency of cyanidation by decreasing elemental sulfur content and by exposing sulfide surfaces - Gonzalo Larrabure; Dhamelyz Silva-Quiñones; Andrew V. Teplyakov; Juan Carlos F. Rodriguez-Reyes (Minerals Engineering, 2023)

The interaction between liver cirrhosis, infection by Streptococcus bovis, and colon cancer - Juan Corredoira; Enrique Miguez; Lara María Mateo; Ricardo Fernández-Rodríguez; José Francisco García-Rodríguez; Alexandre Pérez-González; Ana Sanjurjo; María Victoria Pulian; Blanca Ayuso-García; M. Serrano; M. J. Jove; P. Alonso; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Highly efficient adsorption of furosemide drug by using a Ce0.8Sm0.15Nd0.05O2-δ compound immobilized on massively wasted single use packets - E. Valadez-Renteria; J. Oliva; K.P. Padmasree; A.I. Oliva; V. Rodriguez-Gonzalez (Journal of Environmental Chemical Engineering, 2023)

Observation of large scale precursor correlations between cosmic rays and earthquakes with a periodicity similar to the solar cycle - P. Homola; V. Marchenko; A. Napolitano; R. Damian; R. Guzik; D. Alvarez-Castillo; S. Stuglik; O. Ruimi; O. Skorenok; J. Zamora-Saa; J.M. Vaquero; T. Wibig; et al. (Journal of Atmospheric and Solar-Terrestrial Physics, 2023)

Contrasting reproductive strategies between stress-tolerant and competitive coral taxa - K. G. Bonilla; J. R. Guest; M. V. Baria-Rodriguez (Coral Reefs, 2023)

Multi-level responses of oysters Crassostrea virginica for assessing organochlorine pesticides in a Ramsar coastal lagoon in southern Mexico - Mariana V. Capparelli; Guadalupe Ponce-Vélez; Ricardo Dzul-Caamal; Erick M. Rodriguez-Cab; Marcela Cabrera; Oscar Lucas-Solis; Gabriel M. Moulatlet (Chemosphere, 2023)

Harmonized human biomonitoring in European children, teenagers and adults: EU-wide exposure data of 11 chemical substance groups from the HBM4EU Aligned Studies (2014–2021) - Eva Govarts; Liese Gilles; Laura Rodriguez Martin; Tiina Santonen; Petra Apel; Paula Alvito; Elena Anastasi; Helle Raun Andersen; Anna-Maria Andersson; Lenka Andryskova; Jean-Philippe Antignac; Brice Appenzeller; et al. (International Journal of Hygiene and Environmental Health, 2023)

Spatio-temporal statistical analysis of PM1 and PM2.5 concentrations and their key influencing factors at Guayaquil city, Ecuador - Gladys Rincon; Giobertti Morantes; Heydi Roa-López; Maria del Pilar Cornejo-Rodriguez; Benjamin Jones; Lázaro V. Cremades (Stochastic Environmental Research and Risk Assessment, 2023)
Guayaquil, Ecuador, is in a tropical area on the equatorial Pacific Ocean coast of South America. Since 2008 the city has been increasing its population, vehicle fleet and manufacturing industries. Within the city there are various industrial and urban land uses sharing the same space. With regard to air quality there is a lack of government information on it. Therefore, the research’s aim was to investigate the spatio-temporal characteristics of PM 1 and PM 2.5 concentrations and their main influencing factors. For this, both PM fractions were sampled and a bivariate analysis (cross-correlation and Pearson's correlation), multivariate linear and logistic regression analysis was applied. Hourly and daily PM 1 and PM2.5 were the dependent variables, and meteorological variables, occurrence of events and characteristics of land use were the independent variables. We found 48% exceedances of the PM 2.5 -24 h World Health Organization 2021 threshold’s, which questions the city’s air quality. The cross-correlation function and Pearson’s correlation analysis indicate that hourly and daily temperature, relative humidity, and wind speed have a complex nonlinear relationship with PM concentrations. Multivariate linear and logistic regression models for PM 1 -24 h showed that rain and the flat orography of cement plant sector decrease concentrations; while unusual PM emission events (traffic jams and vegetation-fires) increase them. The same models for PM 2.5 -24 h show that the dry season and the industrial sector (strong activity) increase the concentration of PM 2.5 -24 h, and the cement plant decrease them. Public policies and interventions should aim to regulate land uses while continuously monitoring emission sources, both regular and unusual.

The Challenges of Characterizing the Zooplankton Community Response Following Simulated Spills of Diluted Bitumen into Boreal Lake Limnocorrals - T. A. Black; M. J. Paterson; L. Timlick; J. Cederwall; J. M. Blais; B. Hollebone; D. M. Orihel; V. P. Palace; J. L. Rodriguez-Gil; M. L. Hanson (Bulletin of Environmental Contamination and Toxicology, 2023)

Novel Fusarium wilt resistance genes uncovered in natural and cultivated strawberry populations are found on three non-homoeologous chromosomes - Dominique D. A. Pincot; Mitchell J. Feldmann; Michael A. Hardigan; Mishi V. Vachev; Peter M. Henry; Thomas R. Gordon; Marta Bjornson; Alan Rodriguez; Nicolas Cobo; Randi A. Famula; Glenn S. Cole; Gitta L. Coaker; et al. (Theoretical and Applied Genetics, 2022)
Key Message Several Fusarium wilt resistance genes were discovered, genetically and physically mapped, and rapidly deployed via marker-assisted selection to develop cultivars resistant to Fusarium oxysporum f. sp. fragariae , a devastating soil-borne pathogen of strawberry . Abstract Fusarium wilt, a soilborne disease caused by Fusarium oxysporum f. sp. fragariae , poses a significant threat to strawberry ( Fragaria $$×$$ × ananassa ) production in many parts of the world. This pathogen causes wilting, collapse, and death in susceptible genotypes. We previously identified a dominant gene ( FW1 ) on chromosome 2B that confers resistance to race 1 of the pathogen, and hypothesized that gene-for-gene resistance to Fusarium wilt was widespread in strawberry. To explore this, a genetically diverse collection of heirloom and modern cultivars and octoploid ecotypes were screened for resistance to Fusarium wilt races 1 and 2. Here, we show that resistance to both races is widespread in natural and domesticated populations and that resistance to race 1 is conferred by partially to completely dominant alleles among loci ( FW1 , FW2 , FW3 , FW4 , and FW5 ) found on three non-homoeologous chromosomes (1A, 2B, and 6B). The underlying genes have not yet been cloned and functionally characterized; however, plausible candidates were identified that encode pattern recognition receptors or other proteins known to confer gene-for-gene resistance in plants. High-throughput genotyping assays for SNPs in linkage disequilibrium with FW1 - FW5 were developed to facilitate marker-assisted selection and accelerate the development of race 1 resistant cultivars. This study laid the foundation for identifying the genes encoded by FW1-FW5 , in addition to exploring the genetics of resistance to race 2 and other races of the pathogen, as a precaution to averting a Fusarium wilt pandemic.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Globally, tree fecundity exceeds productivity gradients - Valentin Journé; Robert Andrus; Marie‐Claire Aravena; Davide Ascoli; Roberta Berretti; Daniel Berveiller; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Rafael Calama; Jesús Julio Camarero; et al. (Ecology Letters, 2022)
Lack of tree fecundity data across climatic gradients precludes the analysis of how seed supply contributes to global variation in forest regeneration and biotic interactions responsible for biodiversity. A global synthesis of raw seedproduction data shows a 250‐fold increase in seed abundance from cold‐dry to warm‐wet climates, driven primarily by a 100‐fold increase in seed production for a given tree size. The modest (threefold) increase in forest productivity across the same climate gradient cannot explain the magnitudes of these trends. The increase in seeds per tree can arise from adaptive evolution driven by intense species interactions or from the direct effects of a warm, moist climate on tree fecundity. Either way, the massive differences in seed supply ramify through food webs potentially explaining a disproportionate role for species interactions in the wet tropics.

Beginnings of a plant parasite: early development of Rafflesia consueloae inside its Tetrastigma host - Erika Marie A. Bascos; Edwino S. Fernando; Melizar V. Duya; Lillian Jennifer V. Rodriguez (Planta, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Coral Reef Community Changes in Karimunjawa National Park, Indonesia: Assessing the Efficacy of Management in the Face of Local and Global Stressors - Emma V Kennedy; Julie Vercelloni; Benjamin P Neal; Ambariyanto; Dominic E.P. Bryant; Anjani Ganase; Patrick Gartrell; Kristen Brown; Catherine J.S. Kim; Mu’alimah Hudatwi; Abdul Hadi; Agus Prabowo; et al. (Journal of Marine Science and Engineering, 2020)
Karimunjawa National Park is one of Indonesia’s oldest established marine parks. Coral reefs across the park are being impacted by fishing, tourism and declining water quality (local stressors), as well as climate change (global pressures). In this study, we apply a multivariate statistical model to detailed benthic ecological datasets collected across Karimunjawa’s coral reefs, to explore drivers of community change at the park level. Eighteen sites were surveyed in 2014 and 2018, before and after the 2016 global mass coral bleaching event. Analyses revealed that average coral cover declined slightly from 29.2 ± 0.12% (Standard Deviation, SD) to 26.3 ± 0.10% SD, with bleaching driving declines in most corals. Management zone was unrelated to coral decline, but shifts from massive morphologies toward more complex foliose and branching corals were apparent across all zones, reflecting a park-wide reduction in damaging fishing practises. A doubling of sponges and associated declines in massive corals could not be related to bleaching, suggesting another driver, likely declining water quality associated with tourism and mariculture. Further investigation of this potentially emerging threat is needed. Monitoring and management of water quality across Karimunjawa may be critical to improving resilience of reef communities to future coral bleaching.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Biosolid compost with wood shavings and yard trimmings alleviates stress and improves grain quality in soybean grown in lead polluted soils - Carolina Vergara Cid; Gisele V. Ferreyroa; María L. Pignata; Judith H. Rodriguez (Environmental Science and Pollution Research, 2020)

The Effect of Short-Term Physical Activity on the Oxidative Stress in Rats with Different Stress Resistance Profiles in Cerebral Hypoperfusion - Vladimir V. Chrishtop; Irina K. Tomilova; Tatiana A. Rumyantseva; Elizaveta V. Mikhaylenko; Marco F. Avila-Rodriguez; Liudmila M. Mikhaleva; Vladimir N. Nikolenko; Siva G. Somasundaram; Cecil E. Kirkland; Sergey O. Bachurin; Gjumrakch Aliev (Molecular Neurobiology, 2020)

Microbiome of the deep Lake Baikal, a unique oxic bathypelagic habitat - Pedro J. Cabello‐Yeves; Tamara I. Zemskaya; Alexandra S. Zakharenko; Mariya V. Sakirko; Vyacheslav G. Ivanov; Rohit Ghai; Francisco Rodriguez‐Valera (Limnology and Oceanography, 2020)
Lake Baikal is the deepest lake in the world. Its depth provides the only bathypelagic (> 1000 m deep) freshwater habitat on Earth and its oxic, ultra‐oligotrophic features make it a freshwater counterpart of the deep ocean. Here we have analyzed metagenomes from 1250 and 1350 m deep samples and built 231 metagenome‐assembled genomes (MAGs). We detected high fractions of Thaumarchaeota (ca. 20% of 16S rRNA reads) and members of the candidate phyla radiation (CPR) (3–4.5%). Among the MAGs, we obtained ammonia‐oxidizing archaea (AOA, Nitrosopumilaceae) and bacteria (AOB, Nitrosomonadaceae), and nitrite‐oxidizers (Nitrospirae) indicating very active nitrification. A new clade of freshwater SAR202 Chloroflexi and methanotrophs ( Methyloglobulus ) were also remarkably abundant, the latter reflecting a possible role of methane oxidation as well. Novel species of streamlined and cosmopolitan bacteria such as Ca. Fonsibacter or acI Actinobacteria were more abundant at the surface but also present in deep waters. Conversely, CPRs, Myxococcales, Chloroflexi, DPANN (Diapherotrites, Parvarchaeota, Aenigmarchaeota, Nanoarchaeota and Nanohaloarchaeota) archaea, or Gammaproteobacteria were found only in bathypelagic samples. We noted various important taxonomic and metabolic differences between deep aphotic region of Lake Baikal and marine waters of similar depth: Betaproteobacteriales, CPR, and DPANN superphylum were only found in bathypelagic Baikal, while Deltaproteobacteria, Gammaproteobacteria, or Alphaproteobacteria prevailed in oceanic samples. The genes mediating ammonia and methane oxidation, aromatic compound degradation, or alkane/methanesulfonate monooxygenases were detected in higher numbers in deep Baikal compared to their oceanic counterparts or its own surface. Overall, depth seems to be less relevant than salinity in configuring the microbial community.

A Metabolic Intravascular Platform to Study FDG Uptake in Vascular Injury - F. Franchi; M. Olthoff; J. Krier; C. Noble; M. Al-Hijji; V. Ramaswamy; T. Witt; M. Burke; M. Benscoter; A. Lerman; G. S. Sandhu; M. Rodriguez-Porcel (Cardiovascular Engineering and Technology, 2020)

Opioid-Induced Hyperalgesia Is Associated with Dysregulation of Circadian Rhythm and Adaptive Immune Pathways in the Mouse Trigeminal Ganglia and Nucleus Accumbens - Pan Zhang; Laura S. Moye; Bruce R. Southey; Isaac Dripps; Jonathan V. Sweedler; Amynah Pradhan; Sandra L. Rodriguez-Zas (Molecular Neurobiology, 2019)

Availability of lead in agricultural soils amended with compost of biosolid with wood shavings and yard trimmings - Gisele V. Ferreyroa; Carolina Vergara Cid; Romina A. Verdenelli; María F. Dominchin; José M. Meriles; María L. Pignata; Judith H. Rodriguez (Environmental Science and Pollution Research, 2019)

The Possibility of an Infectious Etiology of Alzheimer Disease - Ghulam M. Ashraf; Vadim V. Tarasov; Alfiya Makhmutovа; Vladimir N. Chubarev; Marco Avila-Rodriguez; Sergey O. Bachurin; Gjumrakch Aliev (Molecular Neurobiology, 2019)

BRAZIL ROAD‐KILL: a data set of wildlife terrestrial vertebrate road‐kills - Clara Grilo; Michely R. Coimbra; Rafaela C. Cerqueira; Priscilla Barbosa; Rubem A. P. Dornas; Larissa O. Gonçalves; Fernanda Z. Teixeira; Igor Pfeifer Coelho; Brenda R. Schmidt; Diana L. K. Pacheco; Gabriela Schuck; Isadora B. Esperando; et al. (Ecology, 2018)
Mortality from collision with vehicles is the most visible impact of road traffic on wildlife. Mortality due to roads (hereafter road‐kill) can affect the dynamic of populations of many species and can, therefore, increase the risk of local decline or extinction. This is especially true in Brazil, where plans for road network upgrading and expansion overlaps biodiversity hotspot areas, which are of high importance for global conservation. Researchers, conservationists and road planners face the challenge to define a national strategy for road mitigation and wildlife conservation. The main goal of this dataset is a compilation of geo‐referenced road‐kill data from published and unpublished road surveys. This is the first Data Paper in the BRAZIL series (see ATLANTIC , NEOTROPICAL , and BRAZIL collections of Data Papers published in Ecology ), which aims make public road‐kill data for species in the Brazilian Regions. The dataset encompasses road‐kill records from 45 personal communications and 26 studies published in peer‐reviewed journals, theses and reports. The road‐kill dataset comprises 21,512 records, 83% of which are identified to the species level (n = 450 species). The dataset includes records of 31 amphibian species, 90 reptile species, 229 bird species, and 99 mammal species. One species is classified as Endangered, eight as Vulnerable and twelve as Near Threatened. The species with the highest number of records are: Didelphis albiventris (n = 1,549), Volatinia jacarina (n = 1,238), Cerdocyon thous (n = 1,135), Helicops infrataeniatus (n = 802), and Rhinella icterica (n = 692). Most of the records came from southern Brazil. However, observations of the road‐kill incidence for non‐Least Concern species are more spread across the country. This dataset can be used to identify which taxa seems to be vulnerable to traffic, analyze temporal and spatial patterns of road‐kill at local, regional and national scales and also used to understand the effects of road‐kill on population persistence. It may also contribute to studies that aims to understand the influence of landscape and environmental influences on road‐kills, improve our knowledge on road‐related strategies on biodiversity conservation and be used as complementary information on large‐scale and macroecological studies. No copyright or proprietary restrictions are associated with the use of this data set other than citation of this Data Paper.

Relationships between variability in precipitation, river levels, and beef cattle production in the Brazilian Pantanal - Ana Gabriela de J. Araujo; Guillermo O. Obregón; Gilvan Sampaio; Antonio Miguel V. Monteiro; Luiz Tadeu da Silva; Balbina Soriano; Carlos Padovani; Daniel Andres Rodriguez; Jelena Maksic; José Felipe Silva Farias (Wetlands Ecology and Management, 2018)

Invasive Rhinosinusitis Caused by Lasiodiplodia theobromae in an Allogeneic Hematopoietic Cell Transplant Recipient Case Report and Review of Literature - Anamaria Rodriguez; Shweta Anjan; Octavio V. Martinez; Lazaros J. Lekakis; Amer Beitinjaneh; Jose F. Camargo; Connie F. C. Gibas; Carmita J. Sanders; Nathan P. Wiederhold; Lilian M. Abbo (Mycopathologia, 2018)

A Novel Short Isoform of Cytosolic PSD-95 Interactor (Cypin) Regulates Neuronal Development - Mihir V. Patel; Przemyslaw Swiatkowski; Munjin Kwon; Ana R. Rodriguez; Keith Campagno; Bonnie L. Firestein (Molecular Neurobiology, 2018)

Adapting clonally propagated crops to climatic changes: a global approach for taro (Colocasia esculenta (L.) Schott) - V. Lebot; V. Tuia; A. Ivancic; G. V. H. Jackson; F. Saborio; G. Reyes; S. Rodriguez; G. Robin; R. Traoré; L. Aboagye; J. Onyeka; W. van Rensburg; et al. (Genetic Resources and Crop Evolution, 2018)

Aerobic interval training reduces vascular resistances during submaximal exercise in obese metabolic syndrome individuals - Ricardo Mora-Rodriguez; V. E. Fernandez-Elias; F. Morales-Palomo; J. G. Pallares; M. Ramirez-Jimenez; J. F. Ortega (European Journal of Applied Physiology, 2017)

Advantage of multispectral imaging with sub-centimeter resolution in precision agriculture: generalization of training for supervised classification - F. Rodriguez-Moreno; J. Kren; F. Zemek; J. Novak; V. Lukas; M. Pikl (Precision Agriculture, 2017)

Spatio-temporal monitoring by ground-based and air- and space-borne lidars of a moderate Saharan dust event affecting southern Europe in June 2013 in the framework of the ADRIMED/ChArMEx campaign - R. Barragan; M. Sicard; J. Totems; J. F. Léon; F. Dulac; M. Mallet; J. Pelon; L. Alados-Arboledas; A. Amodeo; P. Augustin; A. Boselli; J. A. Bravo-Aranda; et al. (Air Quality, Atmosphere & Health, 2017)

Sources of trace metals in PM10 from a petrochemical industrial complex in Northern Mexico - P. F. Rodriguez-Espinosa; R. M. Flores-Rangel; V. Mugica-Alvarez; S. S. Morales-Garcia (Air Quality, Atmosphere & Health, 2017)

Free-living culturable bacteria and protozoa from the rhizoplanes of three floating aquatic plant species - E. Quisehuatl-Tepexicuapan; R. Ferrera-Cerrato; H. V. Silva-Rojas; S. Rodriguez-Zaragoza; A. Alarcón; J. J. Almaraz-Suárez (Plant Biosystems, 2016)

Effectiveness of sequential intravenous-to-oral antibiotic switch therapy in hospitalized patients with gram-positive infection: the SEQUENCE cohort study - D. Rodriguez-Pardo; C. Pigrau; D. Campany; V. Diaz-Brito; L. Morata; I. C. de Diego; L. Sorlí; S. Iftimie; R. Pérez-Vidal; G. García-Pardo; T. Larrainzar-Coghen; B. Almirante (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Thalassospira australica sp. nov. isolated from sea water - Elena P. Ivanova; Mario López-Pérez; Hayden K. Webb; Hooi Jun Ng; Thi Hoang Yen Dang; Natalia V. Zhukova; Valery V. Mikhailov; Russell J. Crawford; Francisco Rodriguez-Valera (Antonie van Leeuwenhoek, 2016)

Loss and gains in ant–plant interactions mediated by extrafloral nectar: fidelity, cheats, and lies - K. Del-Claro; V. Rico-Gray; H. M. Torezan-Silingardi; E. Alves-Silva; R. Fagundes; D. Lange; W. Dáttilo; A. A. Vilela; A. Aguirre; D. Rodriguez-Morales (Insectes Sociaux, 2016)

Estimated Per Capita Water Usage Associated with Different Levels of Water Scarcity Risk in Arid and Semiarid Regions - R. D. G. Rodriguez; F. F. Pruski; V. P. Singh (Water Resources Management, 2016)

First recurrence of Clostridium difficile infection: clinical relevance, risk factors, and prognosis - T. Larrainzar-Coghen; D. Rodriguez-Pardo; M. Puig-Asensio; V. Rodríguez; C. Ferrer; R. Bartolomé; C. Pigrau; N. Fernández-Hidalgo; T. Pumarola; B. Almirante (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Antifungal isolates database of amphibian skin‐associated bacteria and function against emerging fungal pathogens - Douglas C. Woodhams; Ross A. Alford; Rachael E. Antwis; Holly Archer; Matthew H. Becker; Lisa K. Belden; Sara C. Bell; Molly Bletz; Joshua H. Daskin; Leyla R. Davis; Sandra V. Flechas; Antje Lauer; et al. (Ecology, 2015)
Microbial symbionts of vertebrate skin have an important function in defense of the host against pathogens. In particular, the emerging chytrid fungus Batrachochytrium dendrobatidis , causes widespread disease in amphibians but can be inhibited via secondary metabolites produced by many different skin‐associated bacteria. Similarly, the fungal pathogens of terrestrial salamander eggs Mariannaea elegans and Rhizomucor variabilis are also inhibited by a variety of skin‐associated bacteria. Indeed, probiotic therapy against fungal diseases is a recent approach in conservation medicine with growing experimental support. We present a comprehensive Antifungal Isolates Database of amphibian skin‐associated bacteria that have been cultured, isolated, and tested for antifungal properties. At the start, this database includes nearly 2000 cultured bacterial isolates from 37 amphibian host species across 18 studies on five continents: Africa, Oceania, Europe, and North and South America. As the research community gathers information on additional isolates, the database will be updated periodically. The resulting database can serve as a conservation tool for amphibians and other organisms, and provides empirical data for comparative and bioinformatic studies. The database consists of a FASTA file containing 16S rRNA gene sequences of the bacterial isolates, and a metadata file containing information on the host species, life‐stage, geographic region, and antifungal capacity and taxonomic identity of the isolate.

Long‐term hurricane damage effects on tropical forest tree growth and mortality - Edmund V. J. Tanner; Francisco Rodriguez-Sanchez; John R. Healey; Robert J. Holdaway; Peter J. Bellingham (Ecology, 2014)
Hurricane winds can have large impacts on forest structure and dynamics. To date, most evaluations of hurricane impacts have focused on short‐term responses after a hurricane, often lacked pre‐hurricane measurements, and missed responses occurring over longer time scales. Here, we use a long‐term data set (1974–2009, 35 years) of tree stems (>3 cm in diameter at 1.3 m aboveground) in four sites (0.35 ha in total) in montane rain forest (∼1600 m elevation) in Jamaica to investigate the patterns of crown damage in individual stems by Hurricane Gilbert in 1988, and how subsequent growth and mortality were affected by hurricane damage, sprouting, and the incidence of multiple stems. Topographical position on a mountain ridge was the best predictor of crown damage, followed by crown size and species identity. The average diameter growth rate of stems that survived the hurricane was greater than that pre‐hurricane for the whole 21‐yr post‐hurricane period. Growth rates of stems with damaged crowns increased less than those with undamaged crowns; differences in growth rate between damaged and undamaged trees disappeared after 11 years. Hurricane‐damaged stems had two to eight times higher mortality than undamaged stems for 19 years post hurricane. Many stems sprouted shortly after the hurricane, but few sprouts managed to establish (grow to >3 cm diameter at breast height). However, sprouting and multi‐stemming were associated with reduced mortality rate, particularly in damaged trees. From an initial population of 1670 stems in 1974, 54% were still alive in 2009 (21 years after the hurricane). We conclude that despite the high frequency of hurricane damage to tree crowns and the subsequent increased mortality rate in this hurricane‐prone tropical montane forest, many stems will be hit and recover from several hurricanes in their lifetime.

Spatial interpretation of plant parameters in winter wheat - F. Rodriguez-Moreno; V. Lukas; L. Neudert; T. Dryšlová (Precision Agriculture, 2014)

Toxicity assessment through multiple endpoint bioassays in soils posing environmental risk according to regulatory screening values - A. Rodriguez-Ruiz; V. Asensio; B. Zaldibar; M. Soto; I. Marigómez (Environmental Science and Pollution Research, 2014)

Considerations for a Pediatric Biopharmaceutics Classification System (BCS): Application to Five Drugs - Shivani V. Gandhi; William Rodriguez; Mansoor Khan; James E. Polli (AAPS PharmSciTech, 2014)

Trophic ecology of Lampanyctus crocodilus on north‐west Mediterranean Sea slopes in relation to reproductive cycle and environmental variables - E. Fanelli; V. Papiol; J. E. Cartes; O. Rodriguez‐Romeu (Journal of Fish Biology, 2014)
This study examined the population structure, reproductive cycle and feeding pattern of the lanternfish Lampanyctus crocodilus in the Balearic Basin (north‐west Mediterranean Sea) from a depth of 450 to 1800 m and at a seasonal scale. Juveniles were mainly located at shallower depths, but also at deepest stations in autumn, while adults mostly inhabited intermediate depths with their centre of population density (CPD) located at 800–1000 m of depth. The migration of adults to deeper depths was detected in late summer to autumn, probably linked to the occurrence of nepheloid layers at c. 1200 m, which in turn enhances the biomass of the zooplankton prey. The diet was mainly based on euphausiids and mysids, with marked seasonal variations both on the upper (450–800 m) and lower (1000–1800 m), where suprabenthic gammariids and pelagic decapods were also dominant. Stomach fullness increased from winter to autumn on the US , while it had a maximum in spring on the LS , in parallel with high consumption of gelatinous zooplankton, which is probably more available after the phytoplankton bloom in late winter. Reproduction occurred in winter, confirmed by the higher percentage of mature females and high gonadosomatic indices ( I G ) at both depth ranges. Hepatosomatic indices ( I H ) showed an inverse trend to I G on the US, except in autumn, and was almost parallel on the LS, probably attributable to the migration of adults, which determined different temporal schemes in energy use and storage for reproduction on the US v . LS. Consistent with the different patterns observed at the two depth ranges, environmental drivers of fullness ( i.e. feeding intensity) and I G (as a proxy of reproductive cycle) differed on the US and LS. The biomass of mysids and euphausiids was the greatest explanatory variables of fullness on the US and LS, pointing to the increasing feeding intensity when a resource was more available. I H also explained fullness, suggesting that greater feeding intensity in pre‐reproductive periods enabled energy storage in the liver. I G was linked directly ( i.e. mysids) or indirectly ( i.e. surface primary production recorded 2 months before sampling) to food availability, implying a rapid response to vertical food inputs by deep‐sea predators. Also, I G in L. crocodilus was related to population density, which suggests aggregations for reproduction. Estimates of L. crocodilus trophic levels, and of other accompanying mesopelagic fishes, indicated that the species feed through a continuum spanning the third trophic level, confirming the key role of mesopelagic fishes in transferring organic carbon between trophic levels. Trophic niche segregation among mesopelagic species was pronounced and non‐overlapping groups could be distinguished because of the different vertical distribution and migratory behaviour. The study highlights the important role of the benthic boundary layer in sustaining benthopelagic communities in the deep Mediterranean Sea and the need to study the biology of a species throughout its whole depth range and not just at exploited depths ( i.e . fishing grounds).

Genetic variation within a dominant shrub structures green and brown community assemblages - Gregory M. Crutsinger; Mariano A. Rodriguez-Cabal; Adam B. Roddy; Kabir G. Peay; Justin L. Bastow; Allison G. Kidder; Todd E. Dawson; Paul V. A. Fine; Jennifer A. Rudgers (Ecology, 2014)
Two rising challenges in ecology are understanding the linkages between above‐ and belowground components of terrestrial ecosystems and connecting genes to their ecological consequences. Here, we blend these emerging perspectives using a long‐term common‐garden experiment in a coastal dune ecosystem, whose dominant shrub species, Baccharis pilularis , exists as erect or prostrate architectural morphotypes. We explored variation in green (foliage‐based) and brown (detritus‐based) community assemblages, local ecosystem processes, and understory microclimate between the two morphs. Prostrate morphs supported more individuals, species, and different compositions of foliage arthropods, litter microarthropods, and soil bacteria than erect morphs. The magnitude of community compositional differences was maintained from crown to litter to soil. Despite showing strikingly similar responses, green and brown assemblages were associated with different underlying mechanisms. Differences in estimated shrub biomass best explained variation in the green assemblage, while understory abiotic conditions accounted for variation in the brown assemblage. Prostrate morphs produced more biomass and litter, which corresponded with their strong lateral growth in a windy environment. Compared to erect morphs, the denser canopy and thicker litter layer of prostrate morphs helped create more humid understory conditions. As a result, decomposition rates were higher under prostrate shrubs, despite prostrate litter being of poorer quality. Together, our results support the hypothesis that intraspecific genetic variation in primary producers is a key mediator of above‐ and belowground linkages, and that integrating the two perspectives can lead to new insights into how terrestrial communities are linked with ecosystem pools and processes.

Multiple spine boutons are formed after long-lasting LTP in the awake rat - N. I. Medvedev; G. Dallérac; V. I. Popov; J. J. Rodriguez Arellano; H. A. Davies; I. V. Kraev; V. Doyère; M. G. Stewart (Brain Structure and Function, 2014)

Temperature Performance of Different Pervious Pavements: Rainwater Harvesting for Energy Recovery Purposes - Amaya V. Novo; Joseba R. Bayon; Daniel Castro-Fresno; Jorge Rodriguez-Hernandez (Water Resources Management, 2013)

A regulated deficit irrigation strategy for hedgerow olive orchards with high plant density - José E. Fernández; Alfonso Perez-Martin; José M. Torres-Ruiz; María V. Cuevas; Celia M. Rodriguez-Dominguez; Sheren Elsayed-Farag; Ana Morales-Sillero; José M. García; Virginia Hernandez-Santana; Antonio Diaz-Espejo (Plant and Soil, 2013)

Life in a mosaic landscape: anthropogenic habitat fragmentation affects genetic population structure in a frugivorous bat species - Simon P. Ripperger; Marco Tschapka; Elisabeth K. V. Kalko; Bernal Rodriguez-Herrera; Frieder Mayer (Conservation Genetics, 2013)

CHACO outreach project: the development of a primary health care-based medical genetic service in an Argentinean province - C. Z. Barreiro; M. P. Bidondo; J. A. Garrido; J. Deurloo; E. Acevedo; A. Luna; E. Gutiérrez; C. A. Dellamea; C. Picón; K. Torres; M. F. De Castro; M. V. Torrado; et al. (Journal of Community Genetics, 2013)

Assessing water stress in a hedgerow olive orchard from sap flow and trunk diameter measurements - M. V. Cuevas; M. J. Martín-Palomo; A. Diaz-Espejo; J. M. Torres-Ruiz; C. M. Rodriguez-Dominguez; A. Perez-Martin; R. Pino-Mejías; J. E. Fernández (Irrigation Science, 2013)

Spatial impact of projected changes in rainfall and temperature on wheat yields in Australia - A. Potgieter; H. Meinke; A. Doherty; V. O. Sadras; G. Hammer; S. Crimp; D. Rodriguez (Climatic Change, 2013)

A genome-wide association study of breast cancer in women of African ancestry - Fang Chen; Gary K. Chen; Daniel O. Stram; Robert C. Millikan; Christine B. Ambrosone; Esther M. John; Leslie Bernstein; Wei Zheng; Julie R. Palmer; Jennifer J. Hu; Tim R. Rebbeck; Regina G. Ziegler; et al. (Human Genetics, 2013)

Jatropha adoption: a statistical observational study of factors influencing Malian farmers’ decision to grow Jatropha - M. Basinger; J. Chen; F. Jeffrey-Coker; F. S. Rodriguez-Sanchez; T. Singer; V. Modi (Agroforestry Systems, 2012)

Healthy eating index and ovarian cancer risk - Urmila Chandran; Elisa V. Bandera; Melony G. Williams-King; Lisa E. Paddock; Lorna Rodriguez-Rodriguez; Shou-En Lu; Shameka Faulkner; Katherine Pulick; Sara H. Olson (Cancer Causes & Control, 2011)

Effect of the Antimicrobial Peptide Tritrpticin on the In Vitro Viability and Growth of Trichomonas vaginalis - Veronica V. Infante; Alma D. Miranda-Olvera; Luis M. De Leon-Rodriguez; Fernando Anaya-Velazquez; Mayra C. Rodriguez; Eva E. Avila (Current Microbiology, 2011)

Characterization of three sect. Caulopterae species (Baccharis-Asteraceae) inferred from morphoanatomy, polypeptide profiles and spectrophotometry data - M. V. Rodriguez; M. L. Martínez; A. A. Cortadi; A. Bandoni; D. A. Giuliano; S. J. Gattuso; M. A. Gattuso (Plant Systematics and Evolution, 2010)

Family history of various cancers and pancreatic cancer mortality in a large cohort - Eric J. Jacobs; Carmen Rodriguez; Christina C. Newton; Elizabeth B. Bain; Alpa V. Patel; Heather Spencer Feigelson; Michael J. Thun; Eugenia E. Calle (Cancer Causes & Control, 2009)

Use of blood-pressure-lowering medication and risk of prostate cancer in the Cancer Prevention Study II Nutrition Cohort - Carmen Rodriguez; Eric J. Jacobs; Anusila Deka; Alpa V. Patel; Elizabeth B. Bain; Michael J. Thun; Eugenia E. Calle (Cancer Causes & Control, 2009)

One Hundred Questions of Importance to the Conservation of Global Biological Diversity - W. J. SUTHERLAND; W. M. ADAMS; R. B. ARONSON; R. AVELING; T. M. BLACKBURN; S. BROAD; G. CEBALLOS; I. M. CÔTÉ; R. M. COWLING; G. A. B. DA FONSECA; E. DINERSTEIN; P. J. FERRARO; et al. (Conservation Biology, 2009)
We identified 100 scientific questions that, if answered, would have the greatest impact on conservation practice and policy. Representatives from 21 international organizations, regional sections and working groups of the Society for Conservation Biology, and 12 academics, from all continents except Antarctica, compiled 2291 questions of relevance to conservation of biological diversity worldwide. The questions were gathered from 761 individuals through workshops, email requests, and discussions. Voting by email to short‐list questions, followed by a 2‐day workshop, was used to derive the final list of 100 questions. Most of the final questions were derived through a process of modification and combination as the workshop progressed. The questions are divided into 12 sections: ecosystem functions and services, climate change, technological change, protected areas, ecosystem management and restoration, terrestrial ecosystems, marine ecosystems, freshwater ecosystems, species management, organizational systems and processes, societal context and change, and impacts of conservation interventions. We anticipate that these questions will help identify new directions for researchers and assist funders in directing funds.

Proteomic analyses of monocyte-derived macrophages infected with human immunodeficiency virus type 1 primary isolates from Hispanic women with and without cognitive impairment - Dm Toro-Nieves; Y Rodriguez; M Plaud; P Ciborowski; F Duan; J Pérez Laspiur; V Wojna; LM Meléndez (Journal of NeuroVirology, 2009)

Expression of WUSCHEL in Coffea canephora causes ectopic morphogenesis and increases somatic embryogenesis - A. Arroyo-Herrera; A. Ku Gonzalez; R. Canche Moo; F. R. Quiroz-Figueroa; V. M. Loyola-Vargas; L. C. Rodriguez-Zapata; C. Burgeff D′Hondt; V. M. Suárez-Solís; E. Castaño (Plant Cell, Tissue and Organ Culture (PCTOC), 2008)

Characterization of typo-, regio-, and stereo-selectivities of babaco latex lipase in aqueous and organic media - E. Cambon; J. A. Rodriguez; M. Pina; V. Arondel; F. Carriere; F. Turon; J. Ruales; P. Villeneuve (Biotechnology Letters, 2008)

Comparative analysis of neuropeptide cleavage sites in human, mouse, rat, and cattle - Allison N. Tegge; Bruce R. Southey; Jonathan V. Sweedler; Sandra L. Rodriguez-Zas (Mammalian Genome, 2008)

Contrasting photoacclimation costs in ecotypes of the marine eukaryotic picoplankter Ostreococcus - Christophe Six; Zoe V. Finkel; Francisco Rodriguez; Dominique Marie; FrÉdÉric Partensky; Douglas A. Campbell (Limnology and Oceanography, 2008)
Ostreococcus , the smallest known marine picoeukaryote, includes low‐ and high‐light ecotypes. To determine the basis for niche partitioning between Ostreococcus sp. RCC809, isolated from the bottom of the tropical Atlantic euphotic zone, and the lagoon strain Ostreococcus tauri , we studied their photophysiologies under growth irradiances from 15 µmol photons m −2 s −1 to 800 µmol photons m −2 s −1 with a common nutrient replete regime. With increasing growth irradiance, both strains down‐regulated cellular chlorophyll a and chlorophyll b (Chl a and Chl b ) content, increased xanthophyll de‐epoxidation correlated with nonphotochemical excitation quenching, and accumulated lutein. Ribulose‐1,5‐bisphosphate carboxylase/oxygenase content remained fairly stable. Under low‐growth irradiances of 15‐80 µmol photons m −2 s −1 , O. sp. RCC809 had equivalent or slightly higher growth rates, lower Chl a , a higher Chl b : Chl a ratio, and a larger photosystem II (PSII) antenna than O. tauri . O. tauri was more phenotypically plastic in response to growth irradiance, with a larger dynamic range in growth rate, Chl a , photosystem cell content, and cellular absorption cross‐section of PSII. Estimating the amino acid and nitrogen costs for photoacclimation showed that the deep‐sea oceanic O. sp. RCC809 relies largely on lower nitrogen cost changes in PSII antenna size to achieve a limited range of σ‐type light acclimation. O. sp. RCC809, however, suffers photoinhibition under higher light. This limited capacity for photoacclimation is compatible with the stable low‐light and nutrient conditions at the base of the euphotic layer of the tropical Atlantic Ocean. In the more variable, high‐nutrient, lagoon environment, O. tauri can afford to use a higher cost n‐type acclimation of photosystem contents to exploit a wider range of light.

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Spectral and thermal sensing for nitrogen and water status in rainfed and irrigated wheat environments - G. J. Fitzgerald; D. Rodriguez; L. K. Christensen; R. Belford; V. O. Sadras; T. R. Clarke (Precision Agriculture, 2006)

Changing trends in etiology of bacteremia in patients with cancer - A. Safdar; G. H. Rodriguez; M. Balakrishnan; J. J. Tarrand; K. V. I. Rolston (European Journal of Clinical Microbiology & Infectious Diseases, 2006)

Toxicity of Santander Bay Sediments to the Euryhaline Freshwater Oligochaete Limnodrilus hoffmeisteri - P. Rodriguez; J. Arrate; M. Martinez-Madrid; T. B. Reynoldson; V. Schumacher; J. Viguri (Hydrobiologia, 2006)

Successful treatment of septic shock due to pan-resistant Acinetobacter baumannii using combined antimicrobial therapy including tigecycline - F. S. Taccone; H. Rodriguez-Villalobos; D. De Backer; V. De Moor; J. Deviere; J.-L. Vincent; F. Jacobs (European Journal of Clinical Microbiology & Infectious Diseases, 2006)

Selenium Distribution in Topsoils and Plants of a Semi-arid Mediterranean Environment - M.J. Moreno Rodriguez; V. Cala Rivero; R. Jiménez Ballesta (Environmental Geochemistry and Health, 2005)

Parity, Other Reproductive Factors, and Risk of Pancreatic Cancer Mortality in a Large Cohort of U.S. Women (United States) - Lauren R. Teras; Alpa V. Patel; Carmen Rodriguez; Michael J. Thun; Eugenia E. Calle (Cancer Causes & Control, 2005)

Development of a citrus genome-wide EST collection and cDNA microarray as resources for genomic studies - J. Forment; J. Gadea; L. Huerta; L. Abizanda; J. Agusti; S. Alamar; E. Alos; F. Andres; R. Arribas; J. P. Beltran; A. Berbel; M. A. Blazquez; et al. (Plant Molecular Biology, 2005)

FEEDING ECOLOGY OF THE MARINE OTTER ( LUTRA FELINA ) IN A ROCKY SEASHORE OF THE SOUTH OF CHILE - Gonzalo Medina‐Vogel; Claudio Delgado Rodriguez; P. Ricardo E. Alvarez; V. Jose Luis Bartheld (Marine Mammal Science, 2004)
A bstract The marine otter ( Lutra felina ) lives exclusively along exposed rocky shorelines on the South American Pacific coast from Peru (6°S), to Cape Horn, Chile (56°S), and Isla de los Estados, Argentina. L. felina diet and its relationship to prey availability and energy content was assessed by spraint and prey remains analysis, direct observation, and the use of crab pots and fish traps, at four sites on the Valdivian coast in the south of Chile, between June 1999 and June 2000. Based on spraints analysis, the diet was composed of 25 species; 52% (13/25) of the species identified were crustaceans, 40% (10/25) were fish, and 8% (2/25) were mollusks. Crustaceans were found in 78% of 475 spraints, 100% of 929 prey remains, and 90.8% of prey determined by direct observation, fish in 20% of spraints and 9.0% of prey determined by direct observation, and mollusks in 2% of spraints and 0.2% of prey determined by direct observation. Observed seasonal variation in prey availability was reflected in the otter diet. Fourteen prey species were trapped; 43% (6/14) were crustaceans and 57% (8/14) fish, crustaceans were 93% of 566 trapped individuals, fish 7%. L. felina showed opportunistic feeding behavior, selecting prey seasonally according to their availability rather than to their energy input.

Integration of soil solarization with chemical, biological and cultural control for the management of soilborne diseases of vegetables - C. Stevens; V. A. Khan; R. Rodriguez-Kabana; L. D. Ploper; P. A. Backman; D. J. Collins; J. E. Brown; M. A. Wilson; E. C. K. Igwegbe (Plant and Soil, 2003)

Jewish ethnicity and prostate cancer mortality in two large US cohorts - Carmen Rodriguez; Eric J. Jacobs; Alpa V. Patel; Eugenia E. Calle; Heather Spencer Feigelson; Dorna Fakhrabadi-Shokoohi; Michael J. Thun (Cancer Causes & Control, 2002)

Cross Reaction Between a Pan-Candida Genus Probe and Fusarium Spp. in a Fatal Case of Fusarium oxysporum Pneumonia - H. Rodriguez-Villalobos; M. Aoun; C. Heymans; J. De Bruyne; V. Duchateau; J. Verdebout; F. Crokaert (European Journal of Clinical Microbiology & Infectious Diseases, 2002)

Multivitamin use and colon cancer mortality in the Cancer Prevention Study II cohort (United States) - Eric J. Jacobs; Cari J. Connell; Alpa V. Patel; Ann Chao; Carmen Rodriguez; Jennifer Seymour; Marjorie L. McCullough; Eugenia E. Calle; Michael J. Thun (Cancer Causes & Control, 2001)

Physical and chemical processes in the application of CA and/or fumigation - Cecilia V. De Dios; Maria Finesa A. Cosico; Ma. Elvira M. Martinez; D. D. Julian; I. V. Dator; R. L. Tiongson; J. van S. Graver; S. Pratt; C. Reed; Sylvia Allen; G. N. Mbata; T. W. Phillips; et al. (Phytoparasitica, 2001)

Plant species diversity as a driver of early succession in abandoned fields: a multi-site approach - W. H. Van der Putten; S. R. Mortimer; K. Hedlund; C. Van Dijk; V. K. Brown; J. Lepä; C. Rodriguez-Barrueco; J. Roy; T. A. Diaz Len; D. Gormsen; G. W. Korthals; S. Lavorel; et al. (Oecologia, 2000)

Monthly mean pressure reconstructions for Europe for the 1780–1995 period - P.D. Jones; T.D. Davies; D.H. Lister; V. Slonosky; T. Jónsson; L. Bärring; P. Jönsson; P. Maheras; F. Kolyva‐Machera; M. Barriendos; J. Martin‐Vide; R. Rodriguez; et al. (International Journal of Climatology, 1999)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

A comparison between laddermill and treadmill maximal oxygen consumption - M. A. Montoliu; V. Gonzalez; B. Rodriguez; L. Palenciano (European Journal of Applied Physiology, 1997)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Prosthetic joint infection byPasteurella multocida - J. A. Maradona; V. Asensi; J. A. Carton; A. Rodriguez Guardado; J. Lizón Castellano (European Journal of Clinical Microbiology & Infectious Diseases, 1997)

Genetic analysis of nonhistone chromosomal protein inheritance in recombinant inbred mouse strains using two-dimensional electrophoresis - Louis S. Ramagli; James E. Womack; Lewis V. Rodriguez (Biochemical Genetics, 1990)

Influenza A viruses: Combinations of hemagglutinin and neuraminidase subtypes isolated from animals and other sources - V. S. Hinshaw; R. G. Webster; R. J. Rodriguez (Archives of Virology, 1981)

Influenza A viruses: Combinations of hemagglutinin and neuraminidase subtypes isolated from animals and other sources - V. S. Hinshaw; R. G. Webster; R. J. Rodriguez (Archives of Virology, 1979)